Iterative Solution of Linear Programs - Mangasarian, Olvi (University of Wisconsin-Madison Department of Computer Sciences, 1978)
By perturbing a linear program to a quadratic program it is possible to solve the latter in its dual variable space by iterative techniques such as successive over-relaxation (SOR) methods. This provides a solution to the original linear program.